A Conversational Analysis of Turn-Taking in Jay Shetty Podcast - Untari, Jelita; Afrilesa J, Rini; Magria, Vera (Krinok:Jurnal Linguistik Budaya, 2024)
This research analyzes Turn-Taking used in Jay Shetty Podcast. The objectives of the study include (1) to identify the types of turn-taking found in the “Jay Shetty Podcast” (2) to identify the quality of the conversation itself in applying the rules of Turn-Taking mechanism. This research was conducted based on Sacks, Schegloff, and Jefferson’s (1979) theory of Turn-Taking analysis. The method used is descriptive qualitative, which uses words to explain the data obtained from this podcast. Tables and figures are also used to present the result of the research and to make it easier for readers to understand the content of the research.             The results show some findings: there are (21) turn-taking types data found in the Jay Shetty Podcast show, there is one part Address Terms, five parts of Adjacency Pairs, one part of Utterance in Completor, four parts of Incomplection Marker, four parts of Interruption, one part of Possible Pre-Closing, four parts of Overlap, one part of Repair Technique during the show. There are only two types of turn-taking that are not used, namely Post-Completor, and Tag Question.            Using Transition Relevance Place rules for the Jay Shetty Podcast to see whether this conversation violates the rules of turn-taking or not, and find out whether this conversation is quality or not.